2014
DOI: 10.1111/nyas.12609
|View full text |Cite
|
Sign up to set email alerts
|

Are E‐cigarettes a safe and good alternative to cigarette smoking?

Abstract: Electronic cigarettes (E-cigarettes) are devices that can vaporize a nicotine solution combined with liquid flavors instead of burning tobacco leaves. Since their emergence in 2004, E-cigarettes have become widely available, and their use has increased exponentially worldwide. E-cigarettes are aggressively advertised as a smoking cessation aid; as healthier, cheaper, and more socially acceptable than conventional cigarettes. In recent years, these claims have been evaluated in numerous studies. This review exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 40 publications
2
142
0
5
Order By: Relevance
“…E-Cig users are a fast-growing subset of nicotine users who are described as "vapers" rather than smokers, since E-Cigs heat and generate aerosols but do not burn e-liquids. There is considerable controversy regarding the disease risk and toxicity of E-Cigs (112,116,127). However, because E-Cigs do not currently fall under the auspices of the Food and Drug Administration (FDA), they have not undergone the typical toxicological evaluation, followed by human clinical trials that are required of other inhaled products (e.g., inhaled therapeutic agents), and, as such, no safety data exist from either humans or animals.…”
mentioning
confidence: 99%
“…E-Cig users are a fast-growing subset of nicotine users who are described as "vapers" rather than smokers, since E-Cigs heat and generate aerosols but do not burn e-liquids. There is considerable controversy regarding the disease risk and toxicity of E-Cigs (112,116,127). However, because E-Cigs do not currently fall under the auspices of the Food and Drug Administration (FDA), they have not undergone the typical toxicological evaluation, followed by human clinical trials that are required of other inhaled products (e.g., inhaled therapeutic agents), and, as such, no safety data exist from either humans or animals.…”
mentioning
confidence: 99%
“…E-cigarette use significantly reduces the exposure to tobacco-related carcinogens and toxicants when used instead of regular cigarettes (McNeill et al, 2015). However, they are not harmless (Goniewicz et al, 2014; Rom et al, 2014). In many countries, advertising of e-cigarettes is not subject to the same restrictions as those imposed on the advertising of regular cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Even more impressive, the effectiveness of e-cigarettes for smoking cessation or reduction was examined in a survey of 222 smokers who had tried ecigarettes: 31% reported smoking abstinence after 6 months and 67% reported a reduction in the number of cigarettes they smoked (Rom et al, 2015). A study following 40 switchers, showed sustained smoking abstinence after six months in 23%, with 6/9 still using the e-cigarette by the end of the study.…”
Section: The Promise Of E-cigarettesmentioning
confidence: 99%
“…More pragmatic health professionals will see the opportunity to help many smokers to quit. (Rom et al, 2015). But should this be left to prescription controlled by physicians?…”
Section: E-cigarettes -The Ugly Duckling Of Public Health?mentioning
confidence: 99%